Validation of the 40 and 21 items versions of the portrait values questionnaire in Argentina - Beramendi, Maite Regina (2017)
Several studies have measured basic human values across countries using the Portrait Values Questionnaire (PVQ-21 and PVQ-40). However, there are few current validations that use Multidimensional Scaling (MDS) and Confirmatory Factor Analysis (CFA) with a magnifying glass strategy, and almost none in the Latin American context. The objective of this study is to validate both PVQ versions by assessing the configurational verification (MDS) and the confirmatory structure of higher values of Schwartz's model (CFA). The validation analysis of PVQ-40 and PVQ-21 confirm the circular motivational continuum structure of values with some differences. However, PVQ-21 shows better fit indexes in terms of MDS and CFA analyses than PVQ-40. The changes in the motivational continuum circle are explained from the perspective of cultural patterns and historical events in the Argentinean context.